2002
DOI: 10.1016/s0022-5347(05)64663-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Screening For Prostate Cancer In High Risk Families: Early Onset Is A Significant Risk Factor For Disease In First Degree Relatives

Abstract: Our results emphasize the usefulness of PSA screening in high risk families, including those without obvious hereditary features. Furthermore, early onset prostate cancer is a significant risk factor for prostate cancer in first degree relatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 14 publications
0
16
2
1
Order By: Relevance
“…Valeri et al reported that the proportion of relatives with PSA greater than 4 ng/ml and PCa detection was not significantly different according to familial status (sporadic or nonsporadic) [20]. However, our results differed.…”
Section: Discussioncontrasting
confidence: 83%
“…Valeri et al reported that the proportion of relatives with PSA greater than 4 ng/ml and PCa detection was not significantly different according to familial status (sporadic or nonsporadic) [20]. However, our results differed.…”
Section: Discussioncontrasting
confidence: 83%
“…Leur connaissance par une approche génétique est le fondement de nouvelles stratifications des candidats au dépistage du cancer de la prostate [34] et de nouvelles approches chimiopréventives [35]. ◊ SUMMARY Genetic susceptibility to prostate cancer Prostate cancer is the most frequent malignant tumor among men over 50 years old.…”
Section: Discussionunclassified
“…Regardless of uncertainties associated with general population PSA screening, targeted PSA screening of men at high-risk due to family history of prostate cancer may be of benefit (Catalona et al, 2002;Valeri et al, 2002). Familial risk could account for up to 10% of cases, the proportion being much higher at young ages: 43% in men aged 55 or less (Carter et al, 1993).…”
mentioning
confidence: 99%